Vpliv nadzornih inštitucij na uresničevanje pravice do socialne varnosti - Strban, Grega (Delavci in delodajalci, 2015)
The right to social security is fundamental human right, which purpose is to provide income security by public schemes through a process of narrower or broader social solidarity. Next to international, European and constitutional regulation of the right to social security, its national legislative regulation is of utmost importance for the concrete legal situation of an individual. The latter has been considerably modified during the period of reduction of economic activities. When number of active members of the society is reduced and the number of unemployed enhanced, and at the same time taxes and social security contributions are lower than before, States might be tempted to reduce social security expenditure (first as a temporary and later as a structural or permanent measure). Judgments and conclusions of the supervisory bodies on accordance of such measures with international, European and constitutional law are therefore of essential importance.
Keywords: človekove pravice; Evropska unija; socialna varnost